Effect of novel green inhibitor on corrosion and chemical mechanical polishing properties of cobalt in alkaline slurry. (1st August 2022) - Li, Haoran; Zhang, Baoguo; Li, Ye; Wu, Pengfei; Wang, Ye; Xie, Mengchen
Abstract: The galvanic corrosion between copper (Cu) and cobalt (Co) has been widely concerned. Generally, the method of increasing Co corrosion potential is adopted to reduce the corrosion potential difference between Cu/Co. In this paper, the inhibitory mechanism of phytic acid on corrosion of Co, a new green corrosion inhibitor, was studied systematically. The inhibitory effect of phytic acid on Co was studied by dynamic and static electrochemical experiment. The corrosion potential of Co under static condition is higher than that of dynamic condition. The chemical mechanical polishing (CMP) experiments and atomic force microscopy (AFM) tests showed that the introduction of phytic acid increased the material removal rate (from 279 Å/min to 520 Å/min) and surface quality (Rq from 1.74 nm to 0.29 nm) of Co, respectively. The results of Nikon microscope and scanning electron microscope (SEM) showed that phytic acid had inhibitory effect on Co. XPS experimental results showed that the complexation reaction between PA and Co 2+ generated macromolecular substance Co-PA, which was combined with other substances on the surface of Co and formed a new passivation layer to protect the surface of Co from corrosion. The chemical bond between Co 2+ and PA is easy to move, which increases the RR of Co. Highlights: The effect of novel green corrosion inhibitor phytic acid on Co inhibition was studied. The effect of phytic acid on Co surface morphology and CMP was analyzed. The corrosion potential of Co is increased to reduce the galvanic corrosion difference.